2014
DOI: 10.5415/apallergy.2014.4.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells and cytokines of the novel subtypes of helper T cells in asthma

Abstract: BackgroundIn this study, the expression of interleukin-9 (IL-9), IL-17, IL-22, and IL-25 genes that might be the potential predisposing factors for asthma as well as count of innate lymphoid cells (ILCs) as another source of inflammatory cytokines have been evaluated.ObjectiveThe aim of this study was to evaluate the expression of newly identified helper T cells signature cytokines and amount of ILCs.MethodsBlood and sputum samples from 23 patients with moderate to severe asthma and 23 healthy volunteers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Previous studies have found that ILC2s respond to the alarming cytokines IL-25 or IL-33 by producing large amounts of IL-5 and IL-13, which are instrumental for allergic responses in the lung [13]. Thus, we examined the ILC2 compartment, defined by expression of ICOS in the absence of classical lineage markers (ICOS + Lineage – ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that ILC2s respond to the alarming cytokines IL-25 or IL-33 by producing large amounts of IL-5 and IL-13, which are instrumental for allergic responses in the lung [13]. Thus, we examined the ILC2 compartment, defined by expression of ICOS in the absence of classical lineage markers (ICOS + Lineage – ).…”
Section: Resultsmentioning
confidence: 99%
“…Two transcription factors, RORα and GATA3, which are stimulated by IL-7, are required for the development of ILC2s [12]. Upon stimulation with Th2 polarizing cytokines such as IL-25, IL-33, and thymic stromal lymphopoietin (TSLP), mature ILC2s start to produce Th2 cell type cytokines that participate in the progression of allergic asthma [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In one study, we have been found human LinÀ/CD127+/CD161+ ILCs counts were significantly higher in the peripheral blood of the asthmatic patients compared with the healthy individuals. Moreover, we identified a significant elevation of the expression of IL-9, IL-17, IL-22 and IL-25 cytokines in serum and sputum samples of the asthmatic patients compared with normal individuals [100]. Indeed, it has been demonstrated that the elevation of IL-9, IL-17, IL-22 and IL-25 potentially related to severity of asthmatic symptoms.…”
Section: Role Of Ilcs In Asthma and Allergic Inflammationmentioning
confidence: 90%
“…Indeed, it has been demonstrated that the elevation of IL-9, IL-17, IL-22 and IL-25 potentially related to severity of asthmatic symptoms. Furthermore, it was clarified that simultaneous increase in ILCs and eosinophils counts as well as inflammatory cytokines in asthmatic patients may describe the cooperation between ILCs, eosinophils and Th cells in initiation and remaining of allergic responses [100]. In addition, Mjösberg et al have indicated TSLP induces human ILC2 to upregulate directly GATA3 via STAT5 which leading to the secretion of high amounts of type 2 cytokines such as IL-5 and IL-13 [28].…”
Section: Role Of Ilcs In Asthma and Allergic Inflammationmentioning
confidence: 98%
“…Sherkat et al [3] suggest innate lymphoid cells and cytokines of the novel subtypes of helper T cells in asthma. Upper airway diseases may affect the course of asthma.…”
mentioning
confidence: 99%